The trends of Teachers to use The Electronic Educational illustrations at Maths subject . Afield study in Lattakia’s Elementary schools - Khaddar, Nisreen; Morsel, Hiba (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This Research Aims To Know The Trends Of Teacheys To Use The Electronic Educational Illustrations At Maths , And For Achieving The Purposes Of The Research Is Used The Analytic Descriptive Method Through Designing A Questionnaire Consists Of ( 31) Sentences , Distributing On ( 337 ) Teachers In Elementary Schools Of Primary Teaching And The Supreme Results Of This Research Are : - The Existence Of Positive Trends At Teachers To Use The Electronic Educational Illustrations At Maths In Elementary Schools Of Primary Teaching - The Existence Of Differences Which Have A Statistical Signification In The Trends Of Teachers To Use Electronic Educational Illustrations At Maths Are Related A Ccording To The Changing Of Training Courses In Favor Of Teachers Who Follow A Course Or More , And A Ccording To The Different Educational Qualification , In Favor Of The Highest Educational Qualification - The Obsence Of Differences Which Have A Statistical Signification In The Trends Of Educational Illustrations At Maths Are Related To The Difference Of Sex And The Difference Of Experience Year’s Number, And Location Of School